Factorise x3 + 6×2 + 12x + 16

(i) x3 + 6x2 + 12x + 16

x3 + 6x2 + 12x + 8 + 8

Above terms can be written as,

(x3 + (3 × 2 × x2) + (3 × 22 × x) + 23) + 8

We know that, (a + b)3 = a3 + b3 + 3a2b + 3ab2

Now a = x and b = 2

So, (x + 2)3 + 23

We know that, a3 + b3 = (a + b) (a2 – ab + b2)

(x + 2 + 2) ((x + 2)2 – (2 × (x + 2)) + 22)

(x + 4) (x2 + 4 + 4x – 2x – 4 + 4)

(x + 4) (x2 + 2x + 4)

(ii) a3 – 3a2b + 3ab2 – 2b3

Above terms can be written as,

a3 – 3a2b + 3ab2 – b3 – b3

We know that, (a – b)3 = a3 – b3 – 3a2b + 3ab2

So, (a – b)3 + b3

We also know that, a3 – b3 = (a – b) (a2 + ab + b2)

Where, a = a – b, b = b

(a – b – b) ((a – b)2 + (a – b)b + b2)

(a – 2b) (a2 + b2 – 2ab + ab – b2 + b2)

(a – 2b) (a2 + b2 – ab)

More Solutions:

Leave a Comment